2005
DOI: 10.1523/jneurosci.3527-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and Neurodegenerative Alterations in a Transgenic Mouse Model Expressing Human α-Synuclein under Oligodendrocyte Promoter: Implications for Multiple System Atrophy

Abstract: Multiple system atrophy (MSA) is a progressive, neurodegenerative disease characterized by parkinsonism, ataxia, autonomic dysfunction, and accumulation of ␣-synuclein (␣-syn) in oligodendrocytes. To better understand the mechanisms of neurodegeneration and the role of ␣-syn accumulation in oligodendrocytes in the pathogenesis of MSA, we generated transgenic mouse lines expressing human (h) ␣-syn under the control of the murine myelin basic protein promoter. Transgenic mice expressing high levels of h␣-syn dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
271
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(296 citation statements)
references
References 78 publications
23
271
2
Order By: Relevance
“…Although some nuclear staining has been observed in this model, distinct cytoplasmic inclusion-like structures have been consistently identified by confocal and electron microscopy (25,30). The mThy1-␣-syn mice were created and are maintained on a hybrid C57BL/6-DBA/2 background (25).…”
Section: Methodsmentioning
confidence: 99%
“…Although some nuclear staining has been observed in this model, distinct cytoplasmic inclusion-like structures have been consistently identified by confocal and electron microscopy (25,30). The mThy1-␣-syn mice were created and are maintained on a hybrid C57BL/6-DBA/2 background (25).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the constitutive ectopic overexpression of aSyn in oligodendrocytes, a new experimental approach to mimic human MSA was developed [20][21][22]. Three oligodendroglia-specific promotors were used to induce overexpression of human wild type aSyn in transgenic mice, and the outcomes confirmed that aSyn accumulation in oligodendrocytes might trigger neurodegeneration.…”
Section: Overexpression Of Asyn In Oligodendrocytesmentioning
confidence: 98%
“…The San Diego group around Shults and Masliah [22] approached genetic modeling of MSA through overexpression of human aSyn in the mouse brain under the myelin basic protein (MBP) promoter. Through developing several transgenic lines with different degrees of human aSyn overexpression in the mouse oligodendrocytes, they were the first to show that there is a clear cut correlation between the oligodendroglial aSyn dose the severity of the phenotype.…”
Section: The Mbp-asyn Modelmentioning
confidence: 99%
“…Three transgenic (Tg) mouse models in which human wild-type ␣-syn is overexpressed in CNS oligodendrocytes under the control of different promoters were generated. [13][14][15] Two of the three mouse lines showed that the accumulation of ␣-syn as GCIs leads to neuronal degeneration in the mouse CNS.…”
Section: Multiple System Atrophy (Msa) Is a Neurodegenerative Diseasementioning
confidence: 99%